2001
DOI: 10.1007/pl00013973
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Population Genetic Structure of Oryza rufipogon Griff. in Yunnan, China

Abstract: In order to reveal the genetic subdivision within population of common wild rice Wza rufpogm Griff., allozyme analysis was conducted using 22 loci on a typical population from Yunnan Province, China. Non-random distribution of genotypes and/or genetic variability was found among three subpopulations, and the result was further demonstrated by considerable genetic differentiation observed (FsT= 0.206) within the population. Microhabitat selection may not be an important factor in shaping intra-population geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
(36 reference statements)
0
9
1
Order By: Relevance
“…Individuals from Kedah which were grouped together with individuals from Penang were actually genetically closely related to individuals from Kedah (green color rectangular frame) b In contrast to other Oryza species, O. rufipogon shows lower population genetic differentiation. A study by Gao and Zhang (2005) (Gao 2004;Gao and Hong 2000;Gao and Zhang 2005;Gao et al 2001;Song et al 2003a, b) and other Southeast Asia countries (Barbier 1989, Kuroda et al 2002. However, some studies in China showed higher population genetic differentiation of O. rufipogon (Gao et al 2002;Zhou et al 2003) than reported in this current study.…”
Section: B)contrasting
confidence: 63%
“…Individuals from Kedah which were grouped together with individuals from Penang were actually genetically closely related to individuals from Kedah (green color rectangular frame) b In contrast to other Oryza species, O. rufipogon shows lower population genetic differentiation. A study by Gao and Zhang (2005) (Gao 2004;Gao and Hong 2000;Gao and Zhang 2005;Gao et al 2001;Song et al 2003a, b) and other Southeast Asia countries (Barbier 1989, Kuroda et al 2002. However, some studies in China showed higher population genetic differentiation of O. rufipogon (Gao et al 2002;Zhou et al 2003) than reported in this current study.…”
Section: B)contrasting
confidence: 63%
“…It is important to estimate the level of genetic diversity in natural populations of O. rufipogon, since assessment of genetic diversity could be necessary to construct experimental and management plans for searching beneficial genes for rice breeding and conserving genetic resources in natural populations of O. rufipogon. Allozyme variation has been investigated to estimate the level of genetic diversity in natural populations of O. rufipogon (Second 1985;Barbier 1989;Morishima and Barbier 1990;Akimoto et al 1999;Gao and Hong 2000;Gao et al 2001). Average heterozygosities for investigated 40 allozyme loci of the South Asian and Chinese O. rufipogon were 0.25 and 0.19, respectively (Second 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The biological characteristics of the species may be favorable for maintaining the high extent of genetic diversity within the species and thus lead to a considerable adaptation potential [11][12][13]16,24]. However, it would be of great interest to understand the endangered causes and status of the wild rice throughout its entire range by expanding the investigation out of China and comparing the data collected from other worldwide geographical regions.…”
Section: Why O Rufipogon Is Seriously Endangered?mentioning
confidence: 99%
“…Unfortunately, our previous field surveys indicated that this species was at the edge of extinction [3,[7][8][9]. In recent years, we conducted population genetic and molecular ecological studies using multiple genetic markers to obtain deeper insights into levels, distribution and dynamics of genetic diversity within and among natural populations of the species from China [3,[10][11][12][13][14][15][16]. Such investigations of genetic diversity and population structure within the species may not only help to illustrate the evolutionary processes and mechanisms but also provide information useful for developing appropriate and efficient plans for in situ conservation.…”
Section: Introductionmentioning
confidence: 99%